2009
DOI: 10.1007/s11258-009-9714-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of litter quality and climate change along an elevation gradient on litter mass loss in an alpine meadow ecosystem on the Tibetan plateau

Abstract: Knowledge of the response of litter mass loss to climate warming and litter quality in alpine ecosystems is still sparse. Here, we conducted a 507-day litter decomposition experiment along an elevation gradient from 3200 to 3800 m using different litter types to determine the influences of litter quality and climate change on the elemental mass losses and on the temperature sensitivity of litter mass losses (annual percentage decomposition (%) per 1°C temperature difference). Mass losses of C, nitrogen (N), ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 37 publications
2
13
1
Order By: Relevance
“…The mass loss and rate of decomposition varied among the studied land uses, across and within the elevation gradient, which might be due to the litter quality, the presence of varying amounts of water-soluble compounds, physicochemical properties of the litter, and the presence of thick waxy cuticles (pine) [47,48]. A study by Xu et al [49] showed a significant decrease of mass loss with increased elevation, which is comparable with our result. The lowest rate in the forest was attributed to the surface area of pine needles and the cuticles inhibiting the supply of metabolites to the microbial community, which was expected to be the accelerating factor for cropland, shrubland, and grassland.…”
Section: Litter Decomposition In Different Land Use Types Along the Esupporting
confidence: 90%
See 1 more Smart Citation
“…The mass loss and rate of decomposition varied among the studied land uses, across and within the elevation gradient, which might be due to the litter quality, the presence of varying amounts of water-soluble compounds, physicochemical properties of the litter, and the presence of thick waxy cuticles (pine) [47,48]. A study by Xu et al [49] showed a significant decrease of mass loss with increased elevation, which is comparable with our result. The lowest rate in the forest was attributed to the surface area of pine needles and the cuticles inhibiting the supply of metabolites to the microbial community, which was expected to be the accelerating factor for cropland, shrubland, and grassland.…”
Section: Litter Decomposition In Different Land Use Types Along the Esupporting
confidence: 90%
“…A strong positive correlation between changing C and N concentrations of the decomposing litter in this study suggests that C mass loss was promoted by increasing N concentration. Besides decomposition dynamics, C/N, N/P, and C/P ratios are the factors controlling C loss [49]. A change in the potassium concentration was consistent throughout the decomposition period.…”
Section: Nutrient Dynamics During Decompositionmentioning
confidence: 85%
“…Litter quality, defined by C and nitrogen (N) concentrations (Yavitt & Fahey, 1986), C:N ratio (Edmonds, 1980), lignin concentrations (Gholz, Fisher & Prichett, 1985) and lignin:N ratio (Waring & Schlesinger, 1985;Aerts, 1997), also has important implications for the rates of mass loss. However, there is still no universally accepted litter-quality variable for aquatic ecosystems (Kuehn et al, 2011;Su, Kuehn & Phipps, 2015) because the process of litter mass loss depends on complex interactions between soil properties, water properties, climatic factors and litter types (Meentemeyer, 1978;Fierer et al, 2005;Xu et al, 2010;Handa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The model has been used widely in more than 20 countries to obtain accurate calibration and verification results in various ecosystems (Abdalla et al, 2009;Chen et al, 2015;Li et al, 1996Li et al, , 2017Xu et al, 2003;Kariyapperuma et al, 2011;Zhao et al, 2016;Liu et al, 2006;Zhang and Niu, 2016).…”
Section: Dndc Modelmentioning
confidence: 99%